A Case Report of Child with Attention Deficit Hyperactivity Disorder Treated with Individualised Homoeopathic Similimum (Advancements in Homeopathic Research, 2024)
Background: Attention Deficit Hyperactivity  Disorder (ADHD) is currently the most researched  neurodevelopment disorder in childhood, with poor  evidence of confirmatory remedies. Due to its vast  diversity in etiological factors, complexity in its  psychopathology, most system of medicine fails  to provide a long term benefits. The holistic and  individualistic principle of Homoeopathy displays a  vital role treating such condition effectively without  any drug effects or dependence.
Keywords: ADHD; Nux; Vomica; ADHD Rating Scale IV; Individualised Similinum